Epistemological foundations for the study of musical signification: conceptual contributions from the theory of Charles S. Peirce (Revista Argentina de Musicología, 2024)
Musical signification constitutes an emerging phenomenon that is based on complex, dynamic semiotic processes far from equilibrium, through which musical discourses are invested with meaning. It involves the shaping of multiple relationships between the discursive entities given to perception (configurations of significant matter of a sonorous-musical nature) and specific meaning production processes, developed through highly specialized semiotic operations carried out by social actors, giving rise to the generation of particular interpretants on the basis of triadic relations. These relationships make possible the deployment of musical semiosis, activating and weaving a complex network of meaning operations; we find here the hard core in which musical signification is constituted and emerges.In this paper we will discuss some basic semiotic foundations based on various conceptual contributions from the philosophy of Charles Sanders Peirce, in order to ponder their scope and potential for the study of the processes of musical signification, as that, from this perspective, solid epistemological bases can be built to address the production of meaning in the musical field.
Keywords: musical semiotic; Charles S. Pierce; musical signification; semiotic epistemology; musical semiosis